Bahasa Indonesia Kekinian: Pergeseran dan Kreativitas Pembentukan Kata Melalui Akronim, Blending, dan Kliping di Media Sosial - Maela Nikmatul Zuroh; Muhammad Hasbullah Ridwan (Ruang Kata, 2026)
The rise of social media has influenced the use of Indonesian, particularly through the emergence of new vocabulary among the younger generation. This study aims to identify word-formation processes—specifically acronyms, blending, and clipping—in contemporary Indonesian used on social media and to describe their impact on the language's evolution in the digital era. Employing a qualitative descriptive method, the study draws data from posts, captions, and comments on TikTok and Instagram between January and May 2026. Data were collected using "listen-and-note" techniques and subsequently analyzed through stages of reduction, classification, interpretation, and conclusion drawing. The results reveal 15 terms formed through these processes: acronyms (mager, gabut, fomo, POV), blends (salting, healing, bestie, red flag, green flag), and clippings (relate, halu, spill, delulu, core). Additionally, a semantic shift was observed in the word *aura* within the context of digital communication. These findings demonstrate that social media serves as a productive space for linguistic creativity while accelerating changes in Indonesian vocabulary. The study underscores that contemporary Indonesian represents an adaptation to technological advancements and digital culture, characterized by innovations in both form and meaning.